Dental Research Waste in Design, Analysis, and Reporting: A Scoping Review. (March 2021) - Pandis, N.; Fleming, P.S.; Katsaros, C.; Ioannidis, J.P.A.
Research waste is highly prevalent across biomedical investigations. We aimed to assess the evidence on the extent of research waste in dental research. We performed a scoping review of empirical evaluations of dental studies assessing the prevalence and impact of limitations in design, conduct, analysis, and reporting of research. PubMed was searched using specific terms to retrieve studies dealing with design, conduct, analysis, and reporting of studies in dentistry, with no year or language restrictions. Of the 1, 807 publications identified from the search and from manual searches, 71 were included in this review. The topic and article selection was based on the expert opinion of the authors. The existing evidence suggests that, although there are improvements over time, substantial deficiencies in all areas (design, conduct, analysis, reporting) were prevalent in dental research publications. Waste in research is a multifaceted problem without a simple solution. However, an appreciation of optimal research design and execution is a prerequisite and should be underpinned by policies that include appropriate training in research methods and properly aligned incentives.